2019
DOI: 10.7819/rbgn.v0i0.3955
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Technological Products and Services for Different Consumer Profiles: An analysis using the Technology Adoption Propensity Scale

Abstract: Purpose-To evaluate how different consumer profiles react to the adoption of new technologies through the replication and validation of the TAP scale in Brazil. Design/methodology/approach-We designed a descriptive study of a quantitative nature applied through a survey. Exploratory and confirmatory factorial analysis procedures were performed in order to validate the scale. We used t tests to check for statistical differences between consumer profiles. Findings-The TAP scale proved to be a valid and reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…TAP consists of 14 items (Ratchford and Barnhart, 2012). A previous study has shown that it is a valid and reliable scale for different cultural groups in America and Brazil (Bittencourt et al, 2018). The trust scales (DT1-DT4) were adapted from Cheng and Loi (2014), while curiosity scales (DC1-DC6) were adapted from Mehmetoglu (2012) and Litvin and Mouri (2009).…”
Section: Impact Of Consumers' Attitudesmentioning
confidence: 99%
“…TAP consists of 14 items (Ratchford and Barnhart, 2012). A previous study has shown that it is a valid and reliable scale for different cultural groups in America and Brazil (Bittencourt et al, 2018). The trust scales (DT1-DT4) were adapted from Cheng and Loi (2014), while curiosity scales (DC1-DC6) were adapted from Mehmetoglu (2012) and Litvin and Mouri (2009).…”
Section: Impact Of Consumers' Attitudesmentioning
confidence: 99%